A Study of Subliminal Emotion Classification Based on Entropy Features - Shi, Yanjing; Zheng, Xiangwei; Zhang, Min; Yan, Xiaoyan; Li, Tiantian; Yu, Xiaomei (Frontiers in Psychology, 2022)
Electroencephalogram (EEG) has been widely utilized in emotion recognition. Psychologists have found that emotions can be divided into conscious emotion and unconscious emotion. In this paper, we explore to classify subliminal emotions (happiness and anger) with EEG signals elicited by subliminal face stimulation, that is to select appropriate features to classify subliminal emotions. Firstly, multi-scale sample entropy (MSpEn), wavelet packet energy (Ei) and wavelet packet entropy (WpEn) of EEG signals are extracted. Then these features are fed into the decision tree and improved random forest, respectively. The classification accuracy with Ei and WpEn is higher than MSpEn, which shows that Ei and WpEn can be used as effective features to classify subliminal emotions. We compared the classification results of different features combined with the decision tree algorithm and the improved random forest algorithm. The experimental results indicate that the improved random forest algorithm attains the best classification accuracy for subliminal emotions. Finally, subliminal emotions and physiological proof of subliminal affective priming effect is discussed.